AKTUALISASI PRINSIP “DIGUGU LAN DITIRU” DALAM PENGEMBANGAN KUALITAS GURU PAI DI ABAD-21 - M. Afiqul Adib (Yayasan Hurriah, Banda Aceh, 2022)
In the 21st century, the role of education is increasingly becoming the spearhead to prepare society for the challenges of changing times. Students will be more critical in the learning process, so the teacher here must be a figure who can really be relied on, can really be an idol figure for students. The principle in the Javanese language, namely “digugu lan ditiru”, seems to need to be applied by teachers in facing the challenges of the 21st century. This article was written using library research. The information gathering strategy used is documentation. The presentation of the data is carried out according to the existing procedures, then conclusions are also drawn and verification of the research carried out. The results of this study indicate that the method of exemplary and habituation carried out by Islamic religious education teachers greatly influences the psychology of students. If religious values ??are embedded in students and are properly nurtured, they will naturally grow into good personalities.